HIV/AIDS, land-based livelihoods, and land reform in South Africa: Report to the International Food Policy Research Institute and the Department of Land Affairs, South Africa - International Food Policy Research Institute (International Food Policy Research Institute, 2006)
This study is an effort to understand the relationship between HIV/AIDS and land reform in South Africa. It is conceptualised as a longitudinal study covering three years. The study is presently concluding its first year, which has focused on 10 sites in three provinces and the information herein is considered baseline data. Much of the analysis in this report pertains to the nature of land reform projects and land-based livelihoods, and infers the connection to HIV/AIDS rather than observes it directly. The ultimate aim of the research is to generate actionable policy recommendations and programme responses, first of all by answering basic questions such as to what extent and in what way the HIV/AIDS epidemic poses a threat to South Africa’s land reform programme, and secondly by identifying specific ways in which land reform policy and practice should be adjusted. The study is about the impact of HIV/AIDS on land reform and rural livelihoods, and also whether and how land reform can serve as an intervention to mitigate the impact of HIV/AIDS on affected households.